Volumetric changes of the nose and nasal airway 2 years after tooth‐borne and bone‐borne surgically assisted rapid maxillary expansion. (8th July 2013) - Nada, Rania M.; van, Bram; Schols, Jan G. J. H.; Maal, Thomas J. J.; de, Martien J.; Mostafa, Yehya A.; Kuijpers‐Jagtman, Anne M.
<x xml:space="preserve">Abstract</x> This study aimed to assess the effects of bone‐borne and tooth‐borne surgically assisted rapid maxillary expansion on the volumes of the nose and nasal airway 2 yr after maxillary expansion. This prospective cohort study included 32 patients with transverse maxillary hypoplasia. Expansion was performed with a tooth‐borne distractor (Hyrax) in 19 patients and with a bone‐borne distractor [transpalatal distractor (TPD)] in the remaining 13. Cone beam computed tomography scans and three‐dimensional (3D) photographs of the face were acquired before treatment and 22 ± 7 months later, and were used to evaluate the volumes of the nose and nasal airway. Nasal volume increased by 1.01 ± 1.6% in the Hyrax group and by 2.39 ± 2.4% in the TPD group. Nasal airway volume increased by 9.7 ± 5.6% in the Hyrax group and by 12.9 ± 12.7% in the TPD group. Changes in the nasal volume and in the nasal airway volume between the pre‐ and post‐treatment measurements were statistically significant, whereas differences between the treatment groups were not; 22 months after surgically assisted rapid maxillary expansion, the increases in the nasal volume and in the nasal airway volume were comparable between tooth‐borne and bone‐borne devices.